2022
DOI: 10.1186/s13053-022-00244-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors and the uptake of preventative measures in BRCA1/2 pathogenic variant carriers: results of a prospective cohort study

Abstract: Background Women carrying BRCA1/2 pathogenic variants are exposed to elevated risks of developing breast cancer (BC) and are faced by a complex decision-making process on preventative measures, i.e., risk-reducing mastectomy (RRM), and intensified breast surveillance (IBS). In this prospective cohort study we investigated the effect of anxiety, personality factors and coping styles on the decision-making process on risk management options in women with pathogenic variants in BRCA1/2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Concordantly with previous research that used the same personality measure, 17 personality factors were not associated with RRM decision‐making in our study. It remains unclear, if this particular personality measure is not sensitive enough to identify these differences, or if there are in fact none.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Concordantly with previous research that used the same personality measure, 17 personality factors were not associated with RRM decision‐making in our study. It remains unclear, if this particular personality measure is not sensitive enough to identify these differences, or if there are in fact none.…”
Section: Discussionsupporting
confidence: 92%
“…Previously identified factors that were found to influence the decision to undergo RRM were younger age, [11][12][13][14] high perceived but not actual BC risk, 11,13,15 greater anxiety 16,17 and high cancer worry. 15,18 However, some of these studies looked at mixed samples of both cancer-affected and cancer-unaffected women, as well as women with a family history of BC who had not undergone genetic testing at the time of the study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to age and risk-matched controls, patients report a lower perceived breast cancer risk after RRM [100]. In a recent prospective study of 98 BRCA1/2 carriers in Germany, baseline anxiety levels were higher in women opting for RRM but decreased after surgery, whereas women opting for enhanced surveillance tended to have increased levels of anxiety over time [102]. A Dutch study of 96 BRCA1/2 carriers using the standardized BREAST-Q ® questionnaire found that patients undergoing RRM reported lower physical well-being but otherwise similar mean satisfaction with their breasts, psychosocial well-being, and sexual well-being relative to those undergoing enhanced surveillance [103].…”
Section: Psychological Outcomes Following Risk-reducing Mastectomymentioning
confidence: 96%